Child grooming: Sex education as a preventive solution - Khotimah, Rauhul; Casmini, Casmini (Universitas Islam Negeri Raden Intan Lampung, 2024)
Child grooming is sexual, psychological, and physical violence that has now been integrated and mutated with digital technology. Cases of child abuse are of particular concern because they have a long-term impact on children’s development. This research was carried out to provide answers regarding preventive approaches or efforts that can be taken to overcome the phenomenon of child grooming. This research was carried out qualitatively using a phenomenological approach. Data was collected through interviews, observation, and documentation. The data analysis technique was carried out using the Mills & Huberman technique. The validity of this research data applies source triangulation techniques. The results of the research show that child grooming in the form of sexual harassment is more susceptible to girls due to the way they dress less in line with their age, while for boys, it is caused by the physical deficiencies they experience. This research found that there is a need for holistic sex education through approaches to children, parents, teachers, and the social environment in which children live.